2022
DOI: 10.3389/fonc.2022.783079
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs in Colorectal Cancer: Their Functions and Mechanisms

Abstract: Colorectal cancer (CRC) is a common malignancy with high mortality. However, the molecular mechanisms underlying CRC remain unclear. Controversies over the exact functions of non-coding RNAs (ncRNAs) in the progression of CRC have been prevailing for multiple years. Recently, accumulating evidence has demonstrated the regulatory roles of ncRNAs in various human cancers, including CRC. The intracellular signaling pathways by which ncRNAs act on tumor cells have been explored, and in CRC, various studies have id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 171 publications
(148 reference statements)
0
15
0
Order By: Relevance
“…In the context of cancer pathogenesis, miRNA expression has been shown to play a crucial role in the regulation of cell cycle progression, growth, and metabolism, and, thereby, carcinogenesis. For instance, deregulated miRNAs can promote tumorigenesis by both inhibiting the transcription of tumor suppressor genes as well as failing to do so in the case of oncogenes [ 282 ].…”
Section: Aspirin Sensitivity Of Pik3ca -Mutated Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of cancer pathogenesis, miRNA expression has been shown to play a crucial role in the regulation of cell cycle progression, growth, and metabolism, and, thereby, carcinogenesis. For instance, deregulated miRNAs can promote tumorigenesis by both inhibiting the transcription of tumor suppressor genes as well as failing to do so in the case of oncogenes [ 282 ].…”
Section: Aspirin Sensitivity Of Pik3ca -Mutated Crcmentioning
confidence: 99%
“…LncRNAs are defined as transcripts with a length of > 200 nucleotides [ 282 ]. Apart from not being translated, lncRNAs are believed to be processed in the same manner as mRNAs, including transcription by RNA polymerase II as well as post-transcriptional modification, such as 5’ capping, polyadenylation, and splicing [ 283 ].…”
Section: Aspirin Sensitivity Of Pik3ca -Mutated Crcmentioning
confidence: 99%
“…Therefore, uncovering the exact functions and underlying regulatory mechanisms of exosomal ncRNAs in the TME is essential for optimizing current therapeutic strategies. Our previous study concluded the functions and mechanisms of ncRNAs in colorectal cancer (CRC) ( 12 ). This review aims to summarize the interactions between exosomal ncRNAs and TME.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are transcripts longer than 200 nucleotides without translation capability, and they regulate gene expression at multiple levels [ 22 ]. Many lncRNAs have been identified to play important roles in CRC progression [ 23 ]. Accumulating evidence has shown that lncRNAs can protect tumour cells from necroptosis by downregulating the expression of some related proteins [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%